PENGKAJIAN KINERJA SLAG DAN BATU GAMPING PADA PERKERASAN JALAN - Leksminingsih Leksminingsih (Direktorat Bina Teknik Jalan dan Jembatan, 2010)
Pavement materials commonly consist of two important components i.e aggregate ad asphalt. Aggregate with good quality and properties is required for road pavement which directly accommodate traffic load and distribute to layers underneath. In fact, there are some areas where aggregate standard for pavement material is unavailable, alternatively, local materials such as limestone, slag are used. The method used in the research is laboratory experiment by making four kinds of asphalt mix from slag and limestone. Slag and limestone which meet the requirements of standard aggregate can be used as alternative aggregate for asphalt mix. The performance of pavement skid resistance using slag is better compared to limestone. Keyword : road pavement, standard aggregate, slag, limestone, asphalt